2016
DOI: 10.1097/bsd.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Restoration of Sagittal Spinopelvic Alignment After Posterior Lumbar Interbody Fusion in Degenerative Spondylolisthesis

Abstract: Surgical correction of degenerative spondylolisthesis with posterior lumbar interbody fusion and posterior instrumentation resulted in relief of back pain, which may be associated with improvement of sagittal spinopelvic alignment. Surgeons should consider deformity parameters, especially the SA, in the surgical treatment of degenerative spondylolisthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 10 publications
1
32
1
Order By: Relevance
“…An increase in the sacral slope (38.8±7.1 to 43.6±7.2º), an increase in lumbar lordosis (58.0±10.4 to 62.3±9.9º), and a reduction in the angulation of the pelvic inclination (20.2±8.3 to 15.3±7.8º) were recorded in those patients who presented less pain following the surgery (clinical improvement was defined as a change in the visual analog scale for pain of 3 points less than the preoperative evaluation), all of them changes which were statistically significant. 10 In our study, we observed changes in the spino-pelvic parameters similar to those reported by Kong: an increase of sacral slope and lumbar lordosis and a reduction of pelvic tilt, though not statistically significant. Sagittal balance remained within the normal range in all cases.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…An increase in the sacral slope (38.8±7.1 to 43.6±7.2º), an increase in lumbar lordosis (58.0±10.4 to 62.3±9.9º), and a reduction in the angulation of the pelvic inclination (20.2±8.3 to 15.3±7.8º) were recorded in those patients who presented less pain following the surgery (clinical improvement was defined as a change in the visual analog scale for pain of 3 points less than the preoperative evaluation), all of them changes which were statistically significant. 10 In our study, we observed changes in the spino-pelvic parameters similar to those reported by Kong: an increase of sacral slope and lumbar lordosis and a reduction of pelvic tilt, though not statistically significant. Sagittal balance remained within the normal range in all cases.…”
Section: Discussionsupporting
confidence: 75%
“…Kong et al 10 analyzed the changes in the spino-pelvic parameters of patients with degenerative L4-L5 spondylolisthesis who underwent surgical fusion. They observed that following surgical management all the patients presented recovery of the spino-pelvic parameters and improvement of pain as measured by the visual analog scale with an average follow-up of 23.8 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of spondylolisthesis positions the center of gravity of the pelvis towards the anterior position (16,18,19). Nevertheless, increased L 4-5 T but decreased L 4-5 S is found to compensate and prevent the center of gravity displacement (19). Interestingly, L 4-5 I was normal in patients with disk herniation (L 4-5 I = 49.8°) and degenerative disk disease (L 4-5 I = 51.6°), but it was much higher (L 4-5 I = 60.0°) in patients with DLS (24,38), indicating a predisposition to DLS in patients with a higher L 4-5 I (4).…”
Section: Statisticsmentioning
confidence: 85%
“…Extensive studies have been performed on the relationship between coronal imbalance and spinal-pelvic parameters in adult spinal deformity (Kong et al, 2016). However, there are few studies comparing spinal-pelvic parameters and sagittal spinal-pelvic morphology between patients with adolescent idiopathic scoliosis (AIS) and normal adolescents.…”
Section: Introductionmentioning
confidence: 99%